604 Optimising Physical Education Classes in Schools Using Tech-nology: The use of mobile apps for active participation of med-ically exempt students with a focus on skill development and medical rehabilitation (Balneo and PRM Research Journal, 2024)
Abstract: The literature focuses more on healthy students, and the methodologies for organising physical education lessons do not address in depth the problem of physically exempt students who, with time, transform from exempt students into possible patients.This research aims to develop the application "Info-Scutit-Efort" in physical education lessons to facilitate learning, assessment of medically exempt students and their engagement in directed/adapted effort recovery programs in the physical education lesson.The research also aims to extend the use of the application to cover a broader range of needs.  This study highlights the usefulness of the "Info-Scutit-Efort" app to actively and consciously engage 55 medically exempt students (58.2% of the total and 42.8% partially) in physical education lessons.The app, in an enhanced form, offers free and flexible access to different functionalities, in line with all the content of the curriculum and the Medical Checklist, transformed into questions so that the exempted student can access information about previously taught homework, homework taught in real-time, or information about general or particular medical recommendations depending on the diagnosis.In the assessment section, students can access tasks and tests to assess their knowledge, and in the self-assessment section, they can use tools to track their progress.  The assessment provided by the app after the session can give the student a grade for previously taught information if they access the homework from the lessons covered, or it can provide a grade for the current assessment to test active and conscious participation in the lesson just taught as well as information about the indications, recovery programs, received from doctors for various conditions for which students have received medical exemption.The results of the simple linear regression analysis revealed that the relationship between the time spent accessing the application (minutes = 18.60±4.821) and the grade received is significant (p